Mitigating financial stress in a bank-financed economy: Equity injections into banks or purchases of assets? - Michael Kühl (Deutsche Bundesbank, 2014)
This paper compares the consequences of equity injections into banks with purchases of corporate and government bonds in a financial crisis situation using a New Keynesian model in which non-financial firms predominantly take non-market-based debt from banks instead of issuing securities. Our results show that equity injections into banks are more welfare enhancing than asset purchases following a financial shock located in the banking sector. Equity injections remove the frictions that have initiated the stress and, at the same time, relax borrowing conditions. Outright purchases also increase welfare but lower returns with negative effects on banks' profits, while the effect on asset prices to stabilize banks' balance sheets is of minor importance due to the dominance of non-market-based debt. Furthermore, we demonstrate that the origin of the financial shock matters crucially for the efficacy of measures.
Keywords: E44; E58; E61; 330; DSGE Model; Financial Frictions; Financial Accelerator; Unconventional Policy Measures; Asset Purchase Programs; Capital Injections into Banks